Kedudukan Pasal 1320 dan 1338 KUHPerdata dalam Kredit dan Sengketa Konsumen di BPSK - Simanungkalit, Monica Dameria Vicarista; Munawir, Zaini; Zulyadi, Rizkan (Universitas Medan Area, 2024)
The purpose of this study is to analyze the position of Article 1320 and Article 1338 of the Civil Code concerning credit agreements. In addition, this study also aims to evaluate the authority and application of the law by the Consumer Dispute Settlement Agency (BPSK) in resolving consumer disputes related to credit agreements, with a case study based on Decision Number 292/Pdt.Sus.BPSK/2016/PN-Mdn. This study uses a normative juridical method with a qualitative approach through literature and field research. Data was collected from regulations, academic literature, and field documents at the Medan District Court. Descriptive-analytical analysis evaluates the conformity of legal norms with their application in dispute resolution. The results of the study show that the analysis of Article 1320 and Article 1338 of the Civil Code highlights the challenges of the principle of freedom of contract in credit agreements, especially standard agreements that often harm debtors. The evaluation of Decision No. 292/Pdt.Sus.BPSK/2016/PN-Mdn emphasizes the limitations of BPSK's authority in default disputes, highlighting the importance of compliance with the principle of pacta sunt servanda. BPSK reform is needed to ensure justice, transparency, and legal certainty.